D-dimer Assays for the Exclusion of Venous Thromboembolism: Which Test for which Diagnostic Strategy? - de Moerloose, P. (Thrombosis and Haemostasis, 2000)
D-dimer measurement has proven to be very useful to rule out deep vein thrombosis (DVT) and pulmonary embolism (PE) in symptomatic outpatients (1). The problem faced by many physicians is the choice and the position of the D-Dimer tests in the diagnostic work-up of patients suspected of venous thromboembolism (VTE). In the last and present issues of Thrombosis and Haemostasis, two very interesting studies addressing these questions were published.In the first paper (2), de Groot and colleagues evaluated, in a management study, the clinical utility of incorporating the SimpliRED assay in the diagnostic work-up of patients with suspected PE. Of the 245 study subjects, 59 did not receive anticoagulant therapy on the basis of a nondiagnostic lung scan, a normal D-dimer and a non-high clinical probability of PE. In the follow-up, only one patient experienced a thromboembolic event (which can be compared with the 6% of subsequent rate of VTE in the follow-up of the 54 patients with a normal perfusion lung scan). However, if SimpliRED D-dimer would have been used alone as a first exclusion step, 6 of 61 patients with proven PE had been missed (9.8%, 95% CI 3.7-20.2).